The Influence of Organizational Culture, Work Environment and Job Stress on Job Satisfaction Through Organizational Commitment as an Intervening Variable on Employees - Wahyudi, Eko; Sugiono, Edi (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This study aims to analyze the influence of Organizational Culture, Work Environment, and Job Stress on Job Satisfaction through Organizational Commitment as an intervening variable. The data analysis method in this study uses quantitative analysis, specifically descriptive statistical analysis and inferential statistical analysis. The inferential analysis in this study employs PLS-SEM (Partial Least Square – Structural Equation Modeling) with the software SmartPLS 3. The results of the study indicate that Organizational Culture and Work Environment have a positive and significant influence on Job Satisfaction and Organizational Commitment. Meanwhile, Job Stress significantly has a negative impact on Job Satisfaction and Organizational Commitment. Organizational Commitment significantly has a positive influence on Job Satisfaction. Through Organizational Commitment, Organizational Culture significantly has a positive influence on Job Satisfaction. Through Organizational Commitment, the Work Environment positively and significantly affects Job Satisfaction. Through Organizational Commitment, Job Stress is not significant and has a negative influence on Job Satisfaction.